Old Strathcona: Building Character and Commerce in a Preservation District - Wall, Karen (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2002)
Urban spaces of leisure serve to coordinate cultural and economic benefits for local citizens, and contribute to civic profiles in the international competition for prestige and resources. The potential conflicts between cultural and commercial priorities in urban development are particularly marked in the cases of heritage or conservation-oriented districts. The Old Strathcona Historical Preservation District in Edmonton, Alberta provides a case study for an inquiry into how local community has been imagined and expressed through material development processes. The discourse of heritage as both cultural and economic resource is reflected in an analysis of the negotiation among various interests to define Old Strathcona's character and functions. A central point of tension lies between the mandate to conserve and narrate what are primarily community and cultural values, and the economic potential of pragmatic commercial development using that historical content as a marketing feature. As an environment dedicated to consumption, however, Old Strathcona does in fact represent a core element in local civic identity.